1999
DOI: 10.1177/0011128799045002002
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Social Reform: A Progressive Crime Control Agenda

Abstract: The near hegemony of conservative crime control policies is reinforced by a public idea or narrative about crime that citizens find persuasive: “Getting tough” with predatory offenders reduces lawlessness. Progressives have long criticized such ideology, but they have been less successful in advancing ideas capable of directing an alternative policy agenda. For three reasons, we suggest that social support may serve as a public idea that can help organize a progressive approach to crime control. First, the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 17 publications
2
83
0
6
Order By: Relevance
“…Nevertheless, that low selfcontrol is predictive of negative outcomes for prisoner samples is supportive of prior research (Hochstetler & DeLisi, 2005) and adds to the already impressive empirical status of the theory (Pratt & Cullen, 2000). It also illustrates the importance of doing something "for" (support), as opposed to doing something "to" (control), a person to help him or her get on a prosocial behavioral path (see also the discussion by Cullen et al, 1999;Pratt & Cullen, 2005).…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, that low selfcontrol is predictive of negative outcomes for prisoner samples is supportive of prior research (Hochstetler & DeLisi, 2005) and adds to the already impressive empirical status of the theory (Pratt & Cullen, 2000). It also illustrates the importance of doing something "for" (support), as opposed to doing something "to" (control), a person to help him or her get on a prosocial behavioral path (see also the discussion by Cullen et al, 1999;Pratt & Cullen, 2005).…”
Section: Discussionsupporting
confidence: 69%
“…These perceptions include beliefs about how many and what type of individuals are available sources of support for juvenile offenders (Bridges & Steen, 1998;Dukes & Stein, 2001;Gaarder, Rodriguez, & Zatz, 2004). Accounting for perceptions of juvenile offenders' social supports is important because research suggests that offenders who had a large amount of social support were perceived to be more amenable to rehabilitative methods then offenders with fewer supports because the former were thought to have had an already existing network of supports set up to enhance the rehabilitative process (Cullen, Wright, & Chamlin, 1999). Although previous research indicated that there were different aspects of social support that can be measured (i.e., type of support, value of support, and amount of support), this study specifically addressed probation officers' perceptions of the amount of support juvenile offenders receive.…”
Section: Perceptions Of Social Supportmentioning
confidence: 99%
“…The authors are adding three factors that are conceptually consonant with life-course theory and appear to have long-ranged influences on outcomes such as crime (Newcomb, 1997;Stein & Newcomb, 1999). Supportive caregivers nurture and reinforce the development of personal identity attributes that promote resolve to resist temptations encouraged by delinquent peers (Cullen, Wright, & Chamlin, 1999;Lerner, Lerner, De Stefanis, & Apfel, 2001). Instead of attempting the daunting task of presenting an exhaustive list of personal attributes that insulated youths from delinquency, self-esteem and self-efficacy were selected as representatives in the present study.…”
Section: Introductionmentioning
confidence: 99%